Barriers and facilitators to medication adherence among type-2 diabetes mellitus patients in rural Nagpur: a qualitative study - Lalan, Riddhi Hanish; Chavan, Shrinal; Narlawar, Uday; Patil, Sonali; J. S., Anupama (International Journal Of Community Medicine And Public Health, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a growing public health concern in India, with rural populations disproportionately affected by poor glycaemic control. Medication adherence is essential to prevent complications, yet adherence rates remain low in rural settings due to multi factorial barriers. This study aimed to explore the barriers and facilitators influencing medication adherence among T2DM patients in rural Nagpur. Methods: A qualitative study was conducted at the Rural Health Training Centre, Nagpur. Sixteen T2DM patients on oral hypoglycemic agents (OHAs) were recruited via convenience sampling. In-depth interviews were conducted using a semi-structured guide. Data were audio-recorded, transcribed, and analysed through manual thematic analysis. Themes and subthemes were generated to capture key barriers and facilitators. Results: Barriers to medication adherence included knowledge deficits (misunderstanding diabetes and consequences of non-adherence), fear and cultural beliefs (fear of side effects, peer influence), forgetfulness (missed doses or medication purchase), financial constraints, and health system limitations (inadequate follow-up). Facilitators included: family support (emotional and practical), effective healthcare communication (doctor advice, IEC materials), and self-motivation (desire to maintain health, awareness of disease complications), trust in healthcare system (Faith in Government Healthcare Services, Positive Experience) and habit formation and routine integration (medication as daily ritual, use of reminders). Conclusions: Improving medication adherence in rural T2DM patients requires multifaceted interventions. Enhancing patient education, strengthening healthcare communication, and fostering family and community support can significantly improve adherence and health outcomes in underserved rural settings.